Colposcopy in the Primary Health Care: A Scoping Review - Benites-Zapata, Vicente A. (2023)
Aim: Low- and middle-income countries represent nearly 85% of all cervical cancer cases worldwide; thereby, it is extremely important to identify methods to improve the screening process. Therefore, this study aimed to summarize the primary characteristics of studies on accessibility, coverage, patient preferences, and factors associated with patient satisfaction or acceptance of colposcopy in primary healthcare. Methods: A search strategy, based on MeSH, Emtree, and free terms, was run through 5 databases (PubMed, Scopus, Embase, Ovid/Medline, and Web of Science). EndNote 20.1 © and Rayyan QCRI © were used for screening. A preset datasheet was used for data extraction. Results: The systematic search retrieved 1127 references, and after removing duplicates, screening the titles and abstracts, and reviewing the full text, 7 studies were included. The interrater reliability was 77.73% (kappa statistic = 0.1842). Most studies estimated the proportion of women that sought for colposcopy after a previous screening test for human papilloma virus. One study identifies barriers to colposcopy examination in women at risk of developing cervical cancer. Three studies assessed the decentralization of colposcopy from a tertiary healthcare center to a primary care center. Pap smear was the most common first-line screening test, followed by liquid-based cytology sample and visual inspection with acetic acid. Conclusion: Only a few countries have investigated the use of colposcopy in primary care. Thus, barriers and the care structure for this implementation to be successful in reducing cervical cancer incidence and mortality should be identified.